FTAs and the prospects for regional integration in Asia - Razeen Sally (European Centre for International Political Economy (ECIPE), 2006)
Trade policy in Asia has switched from non-discriminatory unilateral liberalisation, reinforced by GATT/ WTO commitments, to discriminatory FTAs. The paper surveys the FTA activity of the major regional players: China, India, the ASEAN countries, Japan and South Korea. It concludes that emerging FTAs are weak and partial. A hub-and-spoke pattern of dirty FTAs will not drive regional economic integration or further integration with the global economy. Rather it could be a force of regional economic disintegration - especially if the multilateral trading system weakens further. At the same time, FTA activity is distracting attention from the WTO, and, more fundamentally, from unilateral liberalisation and domestic structural reforms. Hence Asian trade policies need to be rebalanced, with better-quality FTAs and more focus on the WTO. However, more important than the WTO and FTAs is a fresh spurt of unilateral liberalisation and structural reform - outside trade negotiations.
Keywords: F13; F15; F02; F42; 330; Trade Policy; Regional Economic Integration; International Economic Order; International Policy Coordination and Transmission